Decarboxylative Cross‐Coupling of Mesylates Catalyzed by Copper/Palladium Systems with Customized Imidazolyl Phosphine Ligands1. Issue 10 (5th February 2013) - Song, Bingrui; Knauber, Thomas; Gooßen, Lukas J.
<x xml:space="preserve">Abstract</x> The activation of the inert CO bonds in mesylates through the use of a new class of imidazolyl phosphines allows the decarboxylative coupling of aryl mesylates as well as polysubstituted alkenyl mesylates. Variation of the ligands leads to two complementary methods providing the corresponding biaryls and polysubstituted olefins in good yields.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>